2020
DOI: 10.1016/j.ccell.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Pathway Inhibition Induces TGF-β Signaling to Promote Basal Differentiation in Pancreatic Cancer

Abstract: Oncogenic transformation alters lipid metabolism to sustain tumor growth. We define a mechanism by which cholesterol metabolism controls the development and differentiation of pancreatic ductal adenocarcinoma (PDAC). Disruption of distal cholesterol biosynthesis by conditional inactivation of the rate limiting enzyme Nsdhl or treatment with cholesterol-lowering statins switches glandular pancreatic carcinomas to a basal (mesenchymal) phenotype in mouse models driven by Kras G12D expression and homozygous Trp53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 82 publications
10
126
1
Order By: Relevance
“…Other lipid metabolites, such as cholesterol, were described to regulate PDAC differentiation. Other than the correlation with reduced cholesterol levels in basal-like PDAC subtypes, a sophisticated study of Gabitova-Cornell et al demonstrated that inhibition of cholesterol biosynthesis drives the epithelial-to-mesenchymal transition (EMT) of pancreatic tumor cells and the establishment of a more aggressive tumor phenotype [ 38 ]. Though it has been shown that sphingolipids, including the two central bioactive lipids, ceramide and sphingosine-1-phosphate (S1P), have opposing roles in regulating cancer cell death and survival by evading chemoresistance [ 39 ], cellular and molecular determinants regulating the selectivity of one sphingolipid metabolite over another are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Other lipid metabolites, such as cholesterol, were described to regulate PDAC differentiation. Other than the correlation with reduced cholesterol levels in basal-like PDAC subtypes, a sophisticated study of Gabitova-Cornell et al demonstrated that inhibition of cholesterol biosynthesis drives the epithelial-to-mesenchymal transition (EMT) of pancreatic tumor cells and the establishment of a more aggressive tumor phenotype [ 38 ]. Though it has been shown that sphingolipids, including the two central bioactive lipids, ceramide and sphingosine-1-phosphate (S1P), have opposing roles in regulating cancer cell death and survival by evading chemoresistance [ 39 ], cellular and molecular determinants regulating the selectivity of one sphingolipid metabolite over another are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…By using a GEMM driven by KRAS G12D mutation and homozygous TP53 loss, a recent study demonstrated that inhibition of cholesterol biosynthesis with statins, a widely used inhibitor of the mevalonate pathway, or NAD(P)-dependent steroid dehydrogenase-like enzyme inhibitor can switch glandular pancreatic carcinomas to a basal phenotype. 202 Loss of function of TP53 can drive tumorigenesis via downregulation of cholesterol transporter gene ATP-binding cassette subfamily A member 1 and activation of PI3K/sterol regulatory element-binding protein 2 (SREBP2) maturation. Consequently, the mevalonate pathway, which is responsible for cholesterol and sterol biosynthesis, is upregulated.…”
Section: Metabolism Dysregulation In Pancreatic Cancermentioning
confidence: 99%
“…In PDAC patients, cholesterol biosynthesis is associated with a more differentiated phenotype (classical subtype), while high LDLR expression correlates with a higher risk of tumour recurrence. Interestingly, inhibition of cholesterol synthesis induced a mesenchymal phenotype [ 75 ] while blocking cholesterol uptake via the knock-down of LDLR was able to sensitise PDAC cells to chemotherapy [ 76 , 77 ].…”
Section: Metabolic Reprogramming In Pdacmentioning
confidence: 99%